PERAN PROBLEM BASED LEARNING DALAM MENDORONG KETERAMPILAN KOLABORATIF PESERTA DIDIK PADA PELAJARAN IPAS KELAS 5 SEKOLAH DASAR - nugrahaeni, Andini; Fattimah, Intan; Susanti, Dini; Yusup, Budiman; Rahayu, Galih Dani Septiyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to enhance fifth-grade students' collaboration abilities by implementing the Problem Based Learning (PBL) model in the science and social studies (IPAS) course on the food chain theme at SDN Batujajar 2, West Bandung Regency. The research employed an action research approach using Stringer’s model, consisting of three stages: Look, Think, and Act, conducted over two cycles. The subjects were 30 fifth-grade students. Data were collected through observation using an assessment instrument that measured collaborative skills, including active contribution, listening skills, task distribution, conflict resolution, and giving and receiving feedback. The average collaboration score increased by 7.17 points from 78.58 in the first cycle to 85.75 in the second cycle, according to the data. Every collaboration metric tracked showed improvement. According to these results, PBL helps students build 21st-century skills at the elementary level while also improving their collaboration skills in 21st-century learning.